2020
DOI: 10.1016/j.oraloncology.2020.105045
|View full text |Cite
|
Sign up to set email alerts
|

Resource-sparing curative-intent hypofractionated-accelerated radiotherapy in head and neck cancer: More relevant than ever before in the COVID era

Abstract: Highlights Timely access to RT remains a challenge in low- and middle-income countries. COVID-19 pandemic has disrupted healthcare resources and capacity globally. Radiobiological modelling indicates a somewhat lower α/β ratio for HNSCC. Hypofractionated accelerated RT has significant resource-sparing potential. Such regimens represent a suitable alternative to standard fractionation in HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The 55 Gy at 2.75 Gy per fraction scheme over 4 weeks has also been proposed for other types of H&N cancer in several studies (14,(37)(38)(39)(40)(41)(42). In these studies, the mean age is <60 years, and specific references on elderly patients are not discussed in details However, these studies showed an overall good tolerability and could enhance elderly patients' compliance by reducing the number of needed accesses to the radiotherapy facility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 55 Gy at 2.75 Gy per fraction scheme over 4 weeks has also been proposed for other types of H&N cancer in several studies (14,(37)(38)(39)(40)(41)(42). In these studies, the mean age is <60 years, and specific references on elderly patients are not discussed in details However, these studies showed an overall good tolerability and could enhance elderly patients' compliance by reducing the number of needed accesses to the radiotherapy facility.…”
Section: Discussionmentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak has renewed the interest in HFRT, in general, and for locally advanced H&N cancer, in particular, thanks to the reduction in the risk of getting exposed to the virus by reducing the number of visits to the hospital and the interaction with healthcare professionals ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…This should be considered when designing new multimodal tumor therapies with adapted RT protocols [40]. However, as current studies are carried out with rather small patient cohorts and little is known about long-term effects, especially with regard to normal tissue tolerance [38], additional preclinical research in this area is needed.…”
Section: Icos-l Shows Significantly Enhanced Surface Expression After 5x30gy Only In Hpv-positive Hnscc Cell Linesmentioning
confidence: 99%
“…In recent years, as more and more inhabitants of middle-to low-income countries have been shown to suffer from tumors of the head and neck area, calculations predict that 50% of patients will not be able to gain timely access to therapies while additional resource constraints apply, and thus altered fractionation schemes have been moved even more into the focus of researchers and clinicians. Therefore, an increasing number of studies evaluate hypofractionated-accelerated fractionation schemes also for HNSCC patients [38]. However, as these forms of treatment stretch the tolerance of normal tissue responses, it is important to closely look into these limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation